Legal Responses to Violence Against Football Referees: Criminal Liability and Disciplinary Measures - I Nyoman Aji Duranegara Payuse; Amos Mokorros; I Made Suwitra; I Ketut Sukadana (Sociological Jurisprudence Journal, 2025)
Physical attacks on football referees by players pose significant legal challenges that require analysis within both international and Indonesian legal frameworks. This study examines the legal consequences of such acts by reviewing applicable laws, regulations, and case precedents. The research employs a normative juridical method, focusing on legal norms through statutory and conceptual approaches. Primary data consists of legal regulations, including Indonesian criminal law and FIFA rules, while secondary data includes academic literature, legal doctrine, and case studies. This approach allows for an in-depth examination of the legal framework governing referee assaults. Findings reveal that although Indonesian law criminalizes physical attacks, enforcement is inconsistent due to limited awareness and reluctance to prosecute offenders. FIFA regulations impose disciplinary measures, but their implementation varies. The study concludes that strengthening legal frameworks, enhancing enforcement, and fostering cooperation between sports authorities and legal institutions are crucial to protecting referees and preserving the integrity of football.